PCATool-Brasil versão profissionais: avaliação do atributo acesso de primeiro contato na atenção primária à saúde em municípios do interior do Rio Grande do Sul - Silva, Kauana Flores da (2017)
In Brazil, Primary Health Care is the gateway of users into the health system, based on individual and collective actions, presenting as one of the fundamental principles the universal and equitable access of the population to these actions. In order for this level of attention to be strengthened, guaranteeing access, evaluation is essential, as it allows to leverage available resources according to local demands. Thus, considering the importance of Primary Health Care as a health care provider, with access as an indispensable attribute and evaluation as a tool to change realities, the present study to evaluate the access in APS services of the municipalities that are part of the 4th Regional Health Coordination from the perspective of health professionals. It is a study with a quantitative, transversal approach, carried out in the Primary Health Care services of the 4th Regional Health Coordination of Rio Grande do Sul, composed of the Entre Rios and Verdes Campos Health Regions. Data collection took place between February and July 2015, using computerized Epi Info® 7.0 software, using tablets, with application of the Primary Care Assessment Tool-Brazil professional version. The sample comprised 207 higher-level health professionals. Statistical Analysis System (SAS) version 9.0 was used to analyze the data. The score was dichotomized at low score, if <6.6 or high score, if ≥6.6. The normality of the variables was evaluated by the Shapiro Wilk test. Pearsson's Correlation was used to verify the degree of relationship between First Contact Access items and the score, and Poisson Regression to identify the dependence between the score and its socio-spatial context. The ethical precepts respected Resolution 466/2012. The article 1, a descriptive study in which the attribute First Contact Access obtained a low score (4.68), being the issues related to the time and day of operation of the health unit, the ones that most influenced this result. Article 2, a multilevel study, with contextual and individual variables found low First Contact Access score in most of the municipalities surveyed (83.6%), presenting a level of significance only in the variable population size, in which municipalities with up to five thousand inhabitants Higher prevalence of the attribute. Article 3, a study of trends about access of the elderly in Primary Health Care, shows that access does not prevail as an object of research, related to quality of life and integral care of the elderly, as well as organizational and bureaucratic barriers. Article 4, integrative review on the access of the elderly in this level of attention, showed the Family Health as a facilitator of access, work processes and infrastructure as real barriers to elderly access. In this way, it can be seen that there are still barriers in access, mainly referring to the structure of primary health care services. This study is expected to help in the expansion and quality of the population's access to this level of care.